(untitled) (Bangladesh Journal of Child Health, 2019)
Congenital hypothyroidism is a very common condition in developing world, but myxedema ascites is very rare in pediatric population. We report a case of 13 years old girl with congenital hypothyroidism on irregular thyroxin started on second half of infancy, presented with recurrent ascites excluding all other causes and discuss different aspects of the condition on the basis of literature review. Bangladesh J Child Health 2019; VOL 43 (1) :66-68